2018
DOI: 10.1186/s13023-018-0909-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of the molecular and phenotypic spectrum of Wiedemann-Steiner syndrome in Chinese patients

Abstract: BackgroundWiedemann–Steiner syndrome (WDSTS) is a rare genetic disorder characterized by facial gestalt, neurodevelopmental delay, skeletal anomalies and growth retardation, which is caused by variation of KMT2A gene. To date, only 2 Chinese WDSTS patients have been reported. Here, we report the phenotypes and KMT2A gene variations in 14 unrelated Chinese WDSTS patients and investigate the phenotypic differences between the Chinese and French cohorts. MethodsNext generation sequencing was performed for each pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 23 publications
7
67
0
Order By: Relevance
“…Wiedemann-Steiner syndrome (WDSTS; OMIM #605130) is a rare congenital malformation and neurodevelopmental disorder first described by Wiedemann et al in 1989 and later by Steiner and Marques in 2000 (Wiedemann et al, 1989 ; Steiner and Marques, 2000 ). WDSTS is characterized by intellectual disability, language and motor delays, hypertrichosis cubiti, delayed bone age, and distinct craniofacial features (Koenig et al, 2010 ; Jones et al, 2012 ; Miyake et al, 2016 ; Li et al, 2018 ).…”
Section: Histone Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiedemann-Steiner syndrome (WDSTS; OMIM #605130) is a rare congenital malformation and neurodevelopmental disorder first described by Wiedemann et al in 1989 and later by Steiner and Marques in 2000 (Wiedemann et al, 1989 ; Steiner and Marques, 2000 ). WDSTS is characterized by intellectual disability, language and motor delays, hypertrichosis cubiti, delayed bone age, and distinct craniofacial features (Koenig et al, 2010 ; Jones et al, 2012 ; Miyake et al, 2016 ; Li et al, 2018 ).…”
Section: Histone Methylationmentioning
confidence: 99%
“…Several mutations of KMT2A have been reported, which include single nucleotide missense mutations, non-sense mutations, insertion/deletion alterations that cause frame-shift mutations, and mutations affecting splice site sequences (Li et al, 2018 ). Most of the known mutations alter the reading frame and introduce termination codons in a non-terminal exon.…”
Section: Histone Methylationmentioning
confidence: 99%
“…In addition, genetic variants in KMT2A can also cause Wiedemann‐Steiner syndrome (WDSTS, OMIM #605130) . With the establishment and application of exome sequencing and other NGS in molecular diagnostics the number of identified pathogenic variants in KMT2A is rapidly increasing . KMT2A is a histone methyltransferase that preferentially targets histone H3 lysine 4, known to play fundamental role in controlling transcription with direct effects on embryogenesis and cell‐cycle progression .…”
Section: Chromatin Regulation and Cdls: Clinical And Genetic Featuresmentioning
confidence: 99%
“…The prevalence of feeding difficulty varies in French and Chinese cohorts (31-65%). 12,13 The previous medical history of present case revealed that she had feeding difficulty and tube fed. The main complaint of our patient was neuromotor developmental delay.…”
Section: Discussionmentioning
confidence: 77%